Species‐specific differences in water uptake depth of mature temperate trees vary with water availability in the soil. (15th October 2018) - Brinkmann, N.; Eugster, W.; Buchmann, N.; Kahmen, A.
Abstract: Temperate tree species differ in their physiological sensitivity to declining soil moisture and drought. Although species‐specific responses to drought have often been suggested to be the result of different water uptake depths, empirical evidence for such a mechanism is scarce. Here we test if differences in water uptake depths can explain previously observed species‐specific physiological responses of temperate trees to drought and if the water uptake depth of different species varies in response to declining soil moisture. For this purpose, we employed stable oxygen and hydrogen isotopes of soil and xylem water that we collected over the course of three growing seasons in a mature temperate forest in Switzerland. Our data show that all investigated species utilise water from shallow soil layers during times of sufficient soil water supply. However, Fraxinus excelsior, Fagus sylvatica and Acer pseudoplatanus were able to shift their water uptake to deeper soil layers when soil water availability decreased in the topsoil. In contrast, Picea abies, was not able to shift its water uptake to deeper soil layers. We conclude from our data that more drought‐resistant tree species are able to shift their water uptake to deeper soil layers when water availability in the topsoil is becoming scarce. In addition, we were able to show that water uptake depth of temperate tree species is a trait with high plasticity that needs to be characterised across a range of environmental conditions.